Barriers to testing and management of Mycoplasma genitalium infections in primary care. (October 2019) - McAuliffe, Gary N; Bissessor, Liselle; Basu, Indira; Smith, Susan; Upton, Arlo
Testing and treatment for Mycoplasma genitalium (MG) infections has recently been facilitated by the increasing availability of molecular tests, but the role of testing in community-based populations is not established. Between 15 May 2017 and 22 November 2017, we tested 561 samples from 547 individuals presenting to primary care in Auckland, New Zealand, requesting investigation for sexually transmitted infections, with concurrent sterile pyuria, using the Aptima MG assay (Hologic, San Diego, CA, USA) in order to establish the prevalence of MG in this group, rates of macrolide resistance and audit primary care's capacity to manage infections in line with international guidelines. MG was detected in 55 (10%) samples, and co-pathogens were detected in 24 (44%) MG-positive samples. Macrolide resistance mutations were detected in 22/36 (61%) samples subsequently tested using PlexPCR M. genitalium ResistancePlus (Speedx Pvt Ltd., Sydney, Australia). Empiric azithromycin treatment was given to 18 (33%) patients, and test of cure was performed in 15 (27%) patients. Our pilot study demonstrates that sterile pyuria can be a useful marker to direct testing resources in community settings, but highlights important barriers to management of MG in primary care, including clinician knowledge, high prevalence of macrolide resistance and poor completion rates for test of cure.